A simple simultaneous geometric and intensity correction method for echo-planar imaging by EPI-based phase modulation. - Jr-Yuan Chiou (IEEE Transactions on medical imaging)
A technique, based on echo planar imaging (EPI)-based phase modulation factor maps, is described for correction of EPI distortions resulting from field inhomogeneity. In this paper, a phase modulation factor was employed to remove the distortions. The phase modulation factor was obtained experimentally by collecting EPI images with a spin-echo (TE) spacing, ΔTE, equal to the inter-echo time interval, Ti. Then, the distortions resulting from the field inhomogeneity were removed by modulating the k-space data with the phase modulation factor. One of the advantages of this method is that it requires only a few extra scans to collect the information on field inhomogeneity. The proposed method does not require a phase unwrapping procedure for field inhomogeneity correction and, hence, is easier to implement, compared to other techniques. In addition, it corrects geometric distortion as well as intensity distortions simultaneously, which is robust to external noise or estimation error in severely distorted images. In this work, we also compared the proposed technique with others including, a) interpolation method with EPI-based displacement maps, and b) modulation method with phase modulation factor maps generated from spin-echo images. The results suggest the proposed technique is superior in correcting severely distorted images.